Honeymoons can be hazardous eaudiobook - Flower, Amanda (Amish Matchmaker Mystery, 2022)
Widowed matchmaker Millie Fisher is anything but lonely between her mischievous goats, her quilting circle—and her habit of solving the odd murder or two . . . Millie's decidedly not Amish best friend, Lois Henry, is outspoken, colorful, and so hopelessly romantic, she's had four husbands. Millie doesn't judge, and she also doesn't expect to run into Lois's most recent ex, gambler Gerome Moorhead, in small-town Harvest, Ohio. With him is the very young, new Mrs. Moorhead, aka "Honey Bee." Lois is outraged, but Millie is completely shocked to learn the next day that Gerome is already a widower . . . When a large wood carving at the cozy Munich Chalet falls on "Honey Bee," all eyes turn toward Lois. Who else would want a tourist—a complete stranger—dead? And half of Harvest witnessed Lois's enmity toward the young woman. Suddenly Millie must put aside her sewing needle and flex her sleuthing skills. She's no stranger to a murder investigation, after all, and if she doesn't learn who killed Honey Bee, Lois could go from Millie's boisterous best friend to her horrified prison pen pal . . .